Tren Terkini Dalam Ilmu Komunikasi Di Indonesia: Antara Transformasi Digital Dan Dinamika Budaya - Istialdi Pratama Haris; Yusep Irsyad Najib Setiawan; Rendi Rendi; Noerma Kurnia Fajarwati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This article presents an analysis of the latest trends in communication science in Indonesia, with a focus on the interaction between digital transformation and cultural dynamics. Through a multidimensional approach, we identify how digital technology has changed the communication landscape, influenced people’s communication practices, and triggered changes in communication culture in Indonesia. We also explore the implications of this phenomenon for various aspects of social, political and economic life in Indonesia. Thus, this article provides in-depth insight into how recent developments in communication science represent significant changes in the Indonesian context.